On the Asymptotic Behavior of Solutions of the First Initial Boundary-Value Problems for Parabolic Equations - Nguyen, Manh Hung; Tran, Thi Loan (Ukrains’kyi Matematychnyi Zhurnal, 2003)
We consider the first initial boundary-value problem for a strongly parabolic system on an infinite cylinder with nonsmooth boundary. We prove some results on the existence, uniqueness, and asymptotic behavior of solutions as t → ∞.